El Oficial de Cumplimiento y su influencia en la prevención del lavado activos en la COAC “San Jorge” Ltda., ciudad de Riobamba año 2022. - Miranda Freire, Carola Michelle (2024)
The present investigative project “The Compliance Officer and his influence on the prevention of money laundering at COAC “San Jorge” Cia Ltda., period 2022”, was carried out with the objective of identifying the movements corresponding to the account and obtain adequate control in its use and management. This research addressed Chapter I, where the formulation is presented with its respective approach to the problem, after which the general and specific objective was determined. Chapter II, the opinion of different authors was determined where they support the present research work, which further investigates the conceptualizations of the issues raised. Within Chapter III, the methodology to be used for the realization process will be announced, therefore, the Inductive method is used since it is based on a reasoning study, the approach of this research is mixed since it will work With the quantitative and qualitative approach, two types of research were used: documentary research because we worked with the documentation provided by the entity, and field research due to the constant visits made to the cooperative. The research design is non-experimental. Because there is no manipulation of the variables, the population to work is 100% and on the other hand with greater auxiliaries from the banks and the Deposits to Identify account. In chapter IV, the application of the survey and interview to the Compliance Officer was carried out so that it was possible to determine the adequate compliance and non-compliance of the different functions determined in the law to be executed by the Compliance Officer as well as the mechanisms employees by the Compliance Officer for the prevention of money laundering at COAC “San Jorge” Cia. Ltda.